Humans occupied diverse habitats 70,000 years ago - (:unkn) unknown (My University, 2025)
Homo sapiens spread across the globe owing to our capacity to adapt culturally and technologically to a diverse array of environmental conditions (ecological niches). Successful migrations of H. sapiens out of Africa resulting in long-term populations elsewhere began shortly after 60,000 years ago, when groups moved out of the African continent in a sustained manner. Towards the end of the last ice age, a little more than 20,000 years ago 1 , hunter-gatherers had reached as far as the American continents. What is it about our species that enabled humans to populate the globe? Writing in Nature, Hallett et al. 2 address this question and describe the results of an interdisciplinary study that identifies changes in the ecological niches occupied by H. sapiens hunter-gatherer populations in Africa before their sustained expansion into regions outside the continent.
Keywords: African Research